2015
DOI: 10.1002/lary.25750
|View full text |Cite
|
Sign up to set email alerts
|

Value of a novel PGA-collagen tube on recurrent laryngeal nerve regeneration in a rat model

Abstract: N/A. Laryngoscope, 126:E233-E239, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 18 publications
1
37
0
Order By: Relevance
“…Slides were viewed on a Nikon microscope (Eclipse E200, Nikon, Melville, NY) and images captured with a Leica camera (DFC480, Leica, Buffalo Grove, IL). As previously described, myofiber diameter was evaluated by measuring the lesser fiber diameter using Image J software (NIH, Bethesda, MD) …”
Section: Methodsmentioning
confidence: 99%
“…Slides were viewed on a Nikon microscope (Eclipse E200, Nikon, Melville, NY) and images captured with a Leica camera (DFC480, Leica, Buffalo Grove, IL). As previously described, myofiber diameter was evaluated by measuring the lesser fiber diameter using Image J software (NIH, Bethesda, MD) …”
Section: Methodsmentioning
confidence: 99%
“…In previous studies that used a rat injured-RLN model, 12 or 15 weeks postoperatively was selected as the experimental period. 5,7,8,10 Our preliminary studies suggested that nerve regeneration from proximal to distal stumps could be confirmed by histological examination 8 weeks postoperatively, so this was the experimental period selected to investigate the relatively earlier effect of using RADA16-I hydrogel with a rat injured-RLN model rather than the experimental period described in previous reports.…”
Section: Laryngoscopymentioning
confidence: 99%
“…3 RLNs invaded by tumors require excision; therefore, RLN defects occur in such patients. Although various methods to regenerate defected RLNs have been reported, [4][5][6][7][8][9][10][11] no consistently effective treatments are currently available because they lead to insufficient functional recovery and misdirected innervation. 12 At present, preventing laryngeal muscle atrophy by maintaining nerve continuity is the only feasible treatment method for injured RLNs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations